Late lymphocele infection with Parvimonas micra in a kidney allograft recipient - Rihab Dkhissi; Gabriel Ouellet; Xavier Charmetant; Fanny Buron; Florent Valour; Olivier Rouviere; Xavier Matillon; Emmanuel Morelon (BMC Infectious Diseases)
Abstract Background Lymphocele infection is a frequent and usually early complication following renal transplantation. We report the case of a transplanted patient with a chronic lymphocele that became infected six years after transplantation Parvimonas micra, a commensal of the human oral cavity. Case presentation The patient had a stable lymphocele for six years post-transplantation, as observed through several medical imaging studies, without the need for intervention due to the absence of any impact on graft function. Regarding a six-month progressive decline in general condition, a persistent inflammatory syndrome and a deterioration of renal function, a PET scan revealed a hypermetabolic infiltration behind the lymphocele adjacent to the graft. Bacterial superinfection with Parvimonas micra was diagnosed by an exploratory puncture. The patient had a history of dental periodontal treatments. The initial attempt at treatment with radiological drainage and three months of antibiotic therapy was unsuccessful. Faced with radiological deterioration despite treatment, the patient underwent surgical intervention for lavage with necessary antibiotic therapy for an additional six weeks. He achieved clinical remission, but metabolic activity persists within the site of a residual collection, and the patient remains closely observed. Conclusions Infected lymphoceles should be considered in the differential diagnosis for patients presenting with nonspecific infectious and inflammatory symptoms, regardless of the time elapsed since renal transplantation. The treatment of this complication can be complex.